2021
DOI: 10.1007/s11523-021-00831-4
|View full text |Cite
|
Sign up to set email alerts
|

Making Treatment-Free Remission (TFR) Easier in Chronic Myeloid Leukemia: Fact-Checking and Practical Management Tools

Abstract: In chronic-phase chronic myeloid leukemia (CML), tyrosine kinase inhibitors (TKIs) are the standard of care, and treatmentfree remission (TFR) following the achievement of a stable deep molecular response (DMR) has become, alongside survival, a primary goal for virtually all patients. The GIMEMA CML working party recently suggested that the possibility of achieving TFR cannot be denied to any patient, and proposed specific treatment policies according to the patient's age and risk. However, other international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 103 publications
1
7
0
Order By: Relevance
“…In agreement with the findings from EuroSKI and many other studies [ 1 , 10 , 12 ] we found that the duration of stable DMR was the most relevant prognostic factor for TFR success. In a large real-life cohort of 284 patients, the duration of MR 4.0 or MR 4.5 ≥5 years was the only variable associated to a superior TFR success, with and estimated 5-year TFR rate of 87% and 92%, respectively [ 12 ].…”
supporting
confidence: 93%
“…In agreement with the findings from EuroSKI and many other studies [ 1 , 10 , 12 ] we found that the duration of stable DMR was the most relevant prognostic factor for TFR success. In a large real-life cohort of 284 patients, the duration of MR 4.0 or MR 4.5 ≥5 years was the only variable associated to a superior TFR success, with and estimated 5-year TFR rate of 87% and 92%, respectively [ 12 ].…”
supporting
confidence: 93%
“…At more than 3 years, 65% of patients maintained TFR, and similarly to Euroski trial the duration of DMR was a significant predictive factor of molecular relapse-free survival [ 4 ]. The similarity between the two trials is remarkable considering that a significant proportion of our patients were treated with generic TKIs; the higher rate of molecular remission could be attributed to the better knowledge of discontinuation criteria [ 5 ] that allowed to optimize patients enrollment and harmonized molecular monitoring available from all Argentinean molecular labs [ 6 ]. IL-6 and MCP-1 differed significantly between groups with an overall model accuracy of 87%.…”
mentioning
confidence: 99%
“…32 This finding may have major implications because, regardless of the front-line TKI used, patients who achieve optimal responses at 3 months (early molecular response) have significantly better longterm outcomes, including event-free survival and overall survival, compared with nonoptimal responders. 6 Furthermore, early molecular response is a known predictor of a stable deep molecular response, 33 which is a prerequisite to safely stop treatment (i.e., treatment-free remission), 23 hence with key potential benefits on patients' well-being 34,35 and on a reduction of the financial burden for patients and health care systems because of the high costs of TKIs. 36 Our web-based platform was also well accepted by patients and physicians.…”
Section: Discussionmentioning
confidence: 99%